Deep brain stimulation of the medial forebrain bundle promotes the extinction of active avoidance and is associated with mossy fibber sprouting in the hippocampus - Tapias-Espinosa, Carles; García-Brito, Soleil; Vila-Solés, Laia; Huguet, Gemma; Kádár, Elisabet; Aldavert-Vera, Laura; Segura-Torres, Pilar; Carreras-Badosa, Gemma (Behavioural Brain Research, 2025)
Background Post-traumatic stress disorder (PTSD) causes intrusive symptoms and avoidance behaviours due to dysregulation in various brain regions, including the hippocampus. Deep brain stimulation (DBS) shows promise for refractory PTSD cases. In rodents, DBS improves fear extinction and reduces anxiety-like behaviours, but its effects on active-avoidance extinction remain unexplored. Medial forebrain bundle intracranial self-stimulation (MFB-ICSS) enhances two-way active avoidance (TWAA) conditioning by activating brain regions involved in reinforcement, learning, and memory, including the hippocampus. Methods This study investigates whether reinforcing DBS in the MFB enhances the extinction of conditioned active avoidance responses and examines its effects on hippocampal mossy fibber sprouting using Timm staining. We administered MFB-ICSS treatment following two 50-trial extinction sessions and assessed short-term (24 hours) and long-term (28 days) extinction in a TWAA task in rats. Results MFB-ICSS enhances short-term extinction and accelerates long-term reacquisition of extinction in a spontaneous recovery test. MFB-ICSS also promotes mossy fibber sprouting in the CA2 and CA3 regions of the hippocampus, with CA3 staining positively correlated with the level of extinction. Conclusions These findings suggest that MFB stimulation may enhance extinction and promote neural plasticity mechanisms, including mossy fibber sprouting. However, it does not fully prevent spontaneous recovery, highlighting the need for further optimization of treatment parameters. These results are relevant for PTSD as they suggest a potential enhancement in therapy for extinguishing avoidance responses in patients.
Keywords: active avoidance extinction improvement; deep brain stimulation; hippocampus; intracranial self-stimulation; medial forebrain bundle; mossy fibbers